Activities used by evidence networks to promote evidence-informed decision-making in the health sector- a rapid evidence review - Germán Andrés Alarcón Garavito; Thomas Moniz; Cristián Mansilla; Syka Iqbal; Rozalia Dobrogowska; Fiona Bennin; Shivangi Talwar; Ahmad Firas Khalid; Cecilia Vindrola-Padros (BMC, 2024)
Abstract Background Evidence networks facilitate the exchange of information and foster international relationships among researchers and stakeholders. These networks are instrumental in enabling the integration of scientific evidence into decision-making processes. While there is a global emphasis on evidence-based decision-making at policy and organisational levels, there exists a significant gap in our understanding of the most effective activities to exchange scientific knowledge and use it in practice. The objective of this rapid review was to explore the strategies employed by evidence networks to facilitate the translation of evidence into decision-making processes. This review makes a contribution to global health policymaking by mapping the landscape of knowledge translation in this context and identifying the evidence translation activities that evidence networks have found effective. Methods The review was guided by standardised techniques for conducting rapid evidence reviews. Document searching was based on a phased approach, commencing with a comprehensive initial search strategy and progressively refining it with each subsequent search iterations. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement was followed. Results The review identified 143 articles, after screening 1135 articles. Out of these, 35 articles were included in the review. The studies encompassed a diverse range of countries, with the majority originating from the United States (n = 14), followed by Canada (n = 5), Sweden (n = 2), and various other single locations (n = 14). These studies presented a varied set of implementation strategies such as research-related activities, the creation of teams/task forces/partnerships, meetings/consultations, mobilising/working with communities, influencing policy, activity evaluation, training, trust-building, and regular meetings, as well as community-academic-policymaker engagement. Conclusions Evidence networks play a crucial role in developing, sharing, and implementing high-quality research for policy. These networks face challenges like coordinating diverse stakeholders, international collaboration, language barriers, research consistency, knowledge dissemination, capacity building, evaluation, and funding. To enhance their impact, sharing network efforts with wider audiences, including local, national, and international agencies, is essential for evidence-based decision-making to shape evidence-informed policies and programmes effectively.